Phosflow assessment of PDGFRA phosphorylation state: A guide for tyrosine kinase inhibitor targeted therapy in hypereosinophilia patients. Issue 8 (9th January 2021) - Ranjbaran, Reza; Abbasi, Mojdeh; Rafiei Dehbidi, Gholamreza; Seyyedi, Noorossadat; Behzad‐Behbahani, Abbas; Sharifzadeh, Sedigheh
Abstract: Clonal eosinophilia is a hematologic disorder caused by translocation in growth factor receptor (GFR) genes. Despite the identified molecular mechanisms underlying clonal hypereosinophilia, the distinction between clonal and reactive eosinophilia has remained challenging due to the diversity of partner genes for translocated GFRs. This study aimed to examine the feasibility of phosphoflow cytometry in the diagnosis of clonal hypereosinophilia through evaluating the level of platelet‐derived growth factor receptor alpha (PDGFRA) phosphorylation and its correlation with PDGFRA genetic aberration. Blood samples were collected from 45 hypereosinophilia patients and 10 healthy controls. Using phosphoflow cytometry method, the phosphorylation state of PDGFRA was assessed. The specificity of phosflow results was confirmed by western blotting and eventually compared with qRT‐PCR expression analysis of 3′‐region of PDGFRA. To detect the genetic aberration of PDGFRA, 5′‐rapid amplification of cDNA ends (5′‐RACE) was performed. Phosflow analysis illustrated that 9 of 45 hypereosinophilic patients had higher level of PDGFRA phosphorylation while sequence analysis of 5′‐RACE‐PCR fragments confirmed that in seven cases of them, there was a PDGFRA‐FIP1L1 fusion. We also verified that two of nine patients with hyperposphorylated PDGFRA hold ETV6‐PDGFRA and STRN‐PDGFRA rearrangements. Importantly, nine cases also had significantly higher levels of PDGFRA mRNA expression when compared with healthy controls, and cases with no PDGFRA rearrangement. These findings highlight a robust correlation between hyperphosphorylation state of PDGFRA and aberrant PDGFRA gene fusions. This implicates phosflow as an efficient and reliable technique raising an intriguing possibility that it could replace other genomic and cDNA‐amplification‐based diagnostic approaches with limited effectiveness.